Pedagogical challenges and design of virtual theatre performance: an exploratory case study - Budi Tri Santosa; Diana Hardiyanti (ASSOCIATION FOR SCIENTIFIC COMPUTING ELECTRICAL AND ENGINEERING (ASCEE), 2022)
Covid-19 impacts universities around the world, changing online teaching and learning activities. These changes occur rapidly, causing teachers to look for creative online learning methods, especially learning theatre performances. Virtual theatre learning looks difficult and gives a challenge for teachers during the Covid-19 pandemic. Hence, it is necessary to change the performance mode of production and virtual theatre teaching with the audience's presence through the gadget screens in their homes. This research evaluates and answers the challenges of acting pedagogy that has existed so far and designs a virtual theatre performance format that is certainly different from conventional performances. This research uses the exploratory case study research design. This design was used as a procedure to identify, analyse, and design pedagogical challenges and design a virtual theatre for University of Muhammadiyah Semarang students by giving them a questionnaire. The result shows that collaboration between art and technology is an effective formula for virtual theatre performances. The zoom application and its accompanying features were chosen to be a virtual stage for staging a work. The transition of theatre performances from the traditional to the digital era also impacts the creative team's duties and work responsibilities. It can be observed in the directors, costume stylists, music stylists, lighting stylists, video stylists, stage directors, and production directors. Virtual theatre performances challenge the creativity of actors and creative teams to produce works of art with the help of digital technology. By analyzing the challenge and designing virtual theatre performances, this research can benefit the art community in the future